IMPACT OF CHILD EMPOWERMENT TO DEVELOP LEADERSHIP SKILLS IN STUDENTS AT SCHOOL LEVEL - Sumayya Iram; Dr. Ismat Bano; Shafeeq ur Rehman; Sumera Imran (International Journal of Contemporary Issues in Social Sciences, 2024)
This thesis explores the impact of child commission on the development of leadership chops in scholars within the academy environment. In moment’s fleetly evolving educational geography, leadership chops are decreasingly honored as essential for scholars’ holistic development and unborn success. The conception of child commission, which involves granting children the autonomy and support to take control of their literacy and development, serves as a pivotal strategy in fostering these chops. Through a comprehensive literature review and empirical exploration, this study investigates the relationship between child commission programs and the improvement of leadership rates similar as decision- timber, communication, cooperation, and action among scholars. The exploration methodology includes qualitative and quantitative approaches to dissect the effectiveness of commission enterprise in seminaries, examining both the comprehensions of stakeholders and the measurable issues on pupil leadership development. The findings contribute to being knowledge by relating crucial factors of successful commission programs and pressing their impact on pupil engagement, academic performance, and social-emotional growth. Eventually, this thesis advocates for the integration of child commission strategies into educational programs and practices, aiming to cultivate a generation of confident, able leaders prepared to contribute appreciatively to their communities and beyond.